2023
DOI: 10.3390/pathogens12030466
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Plate Count Can Predict the Presence of Legionella spp. in Cooling Towers

Abstract: Legionella pneumophila (Lp) colonizes aquatic environments and is a potential pathogen to humans, causing outbreaks of Legionnaire’s disease. It is mainly associated with contaminated cooling towers (CTs). Several regulations, including Spanish legislation (Sl), have introduced the analysis of heterotrophic plate count (HPC) bacteria and Legionella spp. (Lsp) in management plans to prevent and control Legionella outbreaks from CTs. The 2003 Sl for CTs (RD 865/2003) considered that concentrations of HPC bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Higher levels of HPC would generally help to predict the presence of Legionella spp., but as HPC colony count units increase, HPC is more likely to suppress L. pneumophila regrowth (Donohue 2021). Although no correlation could be established, other studies found that high colony count units of HPC can be useful for determining the presence of L. pneumophila in cooling towers (Duda et al 2015;Pierre et al 2019;Sanchis et al 2023). Such findings suggest that HPC and L. pneumophila may have similar responses to environmental conditions and parameters in drinking water distribution systems such as water temperature (L. pneumophila growth occurs between 20 and 50 °C) and level of chlorine residual.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of HPC would generally help to predict the presence of Legionella spp., but as HPC colony count units increase, HPC is more likely to suppress L. pneumophila regrowth (Donohue 2021). Although no correlation could be established, other studies found that high colony count units of HPC can be useful for determining the presence of L. pneumophila in cooling towers (Duda et al 2015;Pierre et al 2019;Sanchis et al 2023). Such findings suggest that HPC and L. pneumophila may have similar responses to environmental conditions and parameters in drinking water distribution systems such as water temperature (L. pneumophila growth occurs between 20 and 50 °C) and level of chlorine residual.…”
Section: Discussionmentioning
confidence: 99%